2014
DOI: 10.1007/s12603-014-0505-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sarcopenia in elderly maintenance hemodialysis patients: The impact of different diagnostic criteria

Abstract: A wide prevalence of sarcopenia is observed depending on the method and cutoff limit applied. This may limit extrapolate on to clinical practice. BIA and SKF were the surrogate methods to assess muscle mass with the best concordance with DXA in elderly MHD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
77
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 30 publications
10
77
1
4
Order By: Relevance
“…In addition, the prevalence of sarcopenia by MAMC (9.8%) and BIA (5.9%) evidenced here was similar to that of other studies that used the same methods, such as Gariballa et al by using MAMC in hospitalized patients [38] and Volpato et al by using BIA in institutionalized elderly [18]. In elderly hemodialysis patients, Lamarca et al also found a lower prevalence of sarcopenia when using BIA in comparison with MAMC (respectively 13 versus 31%) both in association with reduced HGS [25]. However, when using an unconventional definition for low muscle mass by BIA (<20th percentile of health individuals), the prevalence rose up to 45%, highlighting the importance of cutoffs adopted when interpreting the prevalence of sarcopenia.…”
Section: O R I G I N a L A R T I C L Esupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, the prevalence of sarcopenia by MAMC (9.8%) and BIA (5.9%) evidenced here was similar to that of other studies that used the same methods, such as Gariballa et al by using MAMC in hospitalized patients [38] and Volpato et al by using BIA in institutionalized elderly [18]. In elderly hemodialysis patients, Lamarca et al also found a lower prevalence of sarcopenia when using BIA in comparison with MAMC (respectively 13 versus 31%) both in association with reduced HGS [25]. However, when using an unconventional definition for low muscle mass by BIA (<20th percentile of health individuals), the prevalence rose up to 45%, highlighting the importance of cutoffs adopted when interpreting the prevalence of sarcopenia.…”
Section: O R I G I N a L A R T I C L Esupporting
confidence: 89%
“…However, studies are still scarce in this population, and they are limited to elderly hemodialysis patients [24,25]. Herein, we aimed to evaluate the prevalence and prognostic power of sarcopenia, assessed by three different criteria, in non-dialysis-dependent (NDD) CKD patients followed up to 40 months.…”
mentioning
confidence: 99%
“…Sarcopenia may be more severe among vulnerable populations, such as those with end-stage renal disease. In hemodialysis patients, the prevalence of sarcopenia was reported to be between 12.7% and 33.7% [4][5][6], and those with sarcopenia have an increased risk of fractures, anxiety, depression, cardiovascular complications, and mortality [4,[7][8][9]. Therefore, early identification and interventions for hemodialysis patients with sarcopenia are essential for effective disease management.…”
Section: Introductionmentioning
confidence: 99%
“…The choices of cutoffs and reference populations are not inconsequential, because the prevalence of sarcopenic obesity in adults in the NHANES varied up to 26-fold depending on the many research definitions available in the literature (21), reflecting overall a profound lack of agreement among scientific societies. Our own attempts to accurately classify sarcopenia in patients on dialysis yielded a similar wide variability (22). There is certainly a need to establish consensus criteria that can be reliably applied across clinical and research settings.…”
mentioning
confidence: 99%